PENGUJIAN pH, GUGUS FUNGSI DAN AKTIVITAS ANTIBAKTERI KRIM BERBAHAN VIRGIN COCONUT OIL (VCO) - Sanjiwani, Ni Made Sukma; Wibawa, Agung Ari Chandra; Sudiarsa, I Wayan; Mirah Mariati, Ni Putu Ayu; Setya Cahyani, I Gusti Ayu Agung Dwita; Pramana, I Made Wisnu Yoga (LPPM, Institut Teknologi Sepuluh Nopember, 2025)
This study aims to determine the pH, determine the functional groups and determine the diameter of the inhibition zone of cream made from VCO. In this study, cream was made with 2 formulations, formula 1 with 15% VCO concentration and formula 2 with 20% VCO concentration. In making the cream, all the ingredients that will be used were weighed first. The oil phase (VCO, vaselin album, stearic acid, span 60, and propyl paraben) was heated to 70°C. The water phase (glycerin, methyl paraben, tween 80, and distilled water) was heated to 70°C. The water phase was gradually incorporated into the oil phase at 70°C. It was then homogenised at 2000 rpm for 15 minutes to cool. Both cream formulas were analysed for pH, functional groups and antibacterial activity. The pH of VCO-based cream in formula 1 has an average pH value of 5.91 and formula 2 has an average pH value of 6.03, so each cream sample has an acidity level with a range of 4.5-6.5. The functional groups found in VCO-based cream formulas 1 and 2 are: C-H bending, C=C stretch (aliphatic and aromatic); C=N, C=O stretch (acids, aldehydes, ketones, amides, esters, anhydrides), CΞC stretch; CΞN, C-H stretch: CH3; CH2, Stretch C-H: C-H; C=C-H; Ar-H. In the range of numbers 3750 - 3000 cm-1 there are functional groups O-H; N-H. Waves 3000-1000 cm-1 have a sharp band shape and strong intensity. The wavenumber 3700-3100 cm-1 has a wide band shape and strong intensity. F2 cream has a larger inhibition zone diameter than F1 cream. The diameter of the inhibition zone of cream F2 is largest at a concentration of 10%, the greater the concentration the less the diameter of the inhibition zone.